2021
DOI: 10.3390/v13040621
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Analysis for Long-Term Sporadic Bovine Viral Diarrhea Transmitted by Calves with an Acute Infection of Bovine Viral Diarrhea Virus 2

Abstract: Bovine viral diarrhea virus (BVDV) is a viral pathogen associated with serious problems in the cattle industry. Cattle persistently infected (PI) with BVDV are mild or asymptomatic; however, they become a source of BVDV transmission to other cattle. Hence, it is important to rapidly identify and remove the PI animals from cattle herds. Whereas cattle acutely infected (AI) with BVDV have various symptoms, yet they generally recover within 3 weeks. However, there is a paucity of information concerning clinical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 48 publications
(19 reference statements)
0
18
0
Order By: Relevance
“…Despite this difference being highly significant on a population level ( 140 ), it cannot be applied to differentiate PI from TI animals in individual cases. Thus, the C t values vary widely, as we observed samples from PI animals providing Ct values above 35 or TI animals showing C t values lower than 20 [( 33 ) and unpublished observation]. Re-sampling the animal at least 3 weeks later resolves the issue in most cases, as the viremic phase in TI animals is usually rather short-lived.…”
Section: Diagnosticsmentioning
confidence: 86%
See 1 more Smart Citation
“…Despite this difference being highly significant on a population level ( 140 ), it cannot be applied to differentiate PI from TI animals in individual cases. Thus, the C t values vary widely, as we observed samples from PI animals providing Ct values above 35 or TI animals showing C t values lower than 20 [( 33 ) and unpublished observation]. Re-sampling the animal at least 3 weeks later resolves the issue in most cases, as the viremic phase in TI animals is usually rather short-lived.…”
Section: Diagnosticsmentioning
confidence: 86%
“…During acute infection lasting ∼2 weeks, virus might be found in various secretions and, thus, might be further transmitted to new, susceptible hosts. However, transient infections on their own are not sufficient to sustain virus circulation for long periods in its host, with a possible exception in large herds [ (30)(31)(32)(33), and unpublished observation], which are rarely found in Switzerland. Nevertheless, transient infections might well-contribute to local transmissions bypassing the temporary absence of susceptible, pregnant animals, finally leading to the infection of naïve, pregnant animals, and to the re-emergence of new PI animals that are required for the long-term survival of this virus in its host population (23).…”
Section: Pestiviruses In Their Host Populationmentioning
confidence: 99%
“…Specifically, the Ct value (28.1: GE copies 280) in the serum from the calf at second sample collection period was matched to the threshold value (Ct value ≦31) of that of a putative BVDV PI animal, but it was more increased from the Ct value (19.3: GE copies 69,000) that was found in the serum at the initial sample collection period. Our previous study suggested that it is important to conduct tests using various analyses throughout multiple sample collection periods in order to accurately diagnose BVDV [35]. Therefore, we collected serum from the calf again 35 days after the initial sample collection.…”
Section: Discussionmentioning
confidence: 99%
“…Calves that are under one month of age do not have a fully functional adaptive immune system [35][36][37]. Therefore, it is important to give provide enough passive immunity via colostrum in order to protect newborn calves from pathogen infection [38].…”
Section: Discussionmentioning
confidence: 99%
“…Bovine viral diarrhoea virus (BVDV) is a pathogen of cattle that manifests with various clinical manifestations. These may include abortion [1], congenital defects, the death of newborn calves [2], enteritis [3,4], respiratory disease, mortality [4], immunosuppression [5], emaciation [3], infertility [6] and mastitis [7].…”
Section: Introductionmentioning
confidence: 99%